Genetic Determinants of Homocysteine and Proinflammatory Cytokines in Henoch–Schönlein purpura: A Study on the Role of MTHFR and MTRR Polymorphisms - Vityala, Yethindra (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Henoch–Schönlein purpura (HSP) remains a disease with an unclear etiology in many patients, which makes prompt diagnosis, treatment, and prevention challenging. During the acute phase of HSP, patients exhibit increased levels of vascular endothelial growth factor, tumor necrosis factor-alpha (TNF-α), and interleukin (IL)-6. This study aimed to assess the levels of proinflammatory cytokines in patients with HSP who had genetically determined hyperhomocysteinemia (HHcy) and received standard basic treatment with folic acid. Materials and Methods: This study included 145 patients with HSP treated at the Department of Hematology of the National Center of Oncology and Hematology, Kyrgyz Republic. Diagnosis was based on clinical and laboratory tests, including complete blood count, urine test, biochemical blood test, hemostasiogram, cytokine and homocysteine level studies, and methylenetetrahydrofolate reductase and methionine synthase reductase gene studies using real-time polymerase chain reaction. Treatment included bed rest, a hypoallergenic diet, anticoagulants, antiplatelet agents, fibrinolysis activators, and steroid hormone drugs at medium doses. Results: The blood serum of patients with cutaneous, articular, abdominal, and renal syndromes of HSP showed a significant increase in IL-6 and TNF-α levels compared with the control group and patients with cutaneous and articular syndromes of HSP (P < 0.001 and P < 0.05, respectively). However, the IL-1β levels were within the normal range. In patients with a generalized form of HSP, treatment resulted in 10% and 18.3% decreases in the concentrations of IL-6 and TNF-α, respectively (P < 0.001). However, the IL-6 level remained above normal values. Conclusion: Proinflammatory cytokines, such as IL-6, TNF-α, and IL-1β, are important in HSP pathogenesis and genetically determined HHcy may serve as a predisposing factor for this condition.